Pop City Korean Popular Culture and the Selling of Place - Youjeong, Oh (Cornell University Press, 2018)
This book examines how Korean television dramas and K-pop music are employed to promote urban and rural regions within South Korea to overseas tourists. Riding the international popularity of Korean entertainment, Korean cities have actively used K-dramas and K-pop idols in advertisements designed to attract foreign tourists to their regions. By examining the process of cultural marketing, this book shows that places can be "sold" just like TV dramas and pop idols by promoting spectacular images rather than substantial physical and cultural qualities.